Sulfide electrolyte composite material, preparation method thereof and all-solid-state battery

By covering the overwriting layer of the amorphous compound on the surface of vulcanic electrolytes, the chemical and electrochemical stability of vulcanizes electrolytes are solved, and a more stable solid-solid interface and higher ionic conductivity are achieved. Efficient application of full solid -state batteries.

CN119381530APending Publication Date: 2025-01-28ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1

Patent Information

Application Number
CN202411512547.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The chemical stability and electrochemical stability of sulfide electrolytes are poor, and they are prone to react with water and oxygen in the air, resulting in structural damage and toxic gases. They will be oxidized and decomposed at high voltages, hindering the conduction of interface ions and increasing interface impedance. .

Method used

The overwhelmed material of an amorphous compound is used to cover the surface of the sulfide solid electrolyte to form a sulfide electrolyte composite material. The covering material includes Limx5yn-1/N, where M is TA, NB, W, or MO, X for F, CL, BR, or I, yn- to various anion, ion conductivity ≥1ms/cm.

Benefits of technology

Effectively suppress the side effects of electrolytes and active materials at high voltage, reduce decomposition products, reduce interface impedance, improve the stability of the solid-solid interface, reduce water oxygen adsorption in the air, improve chemical stability, and maintain high ion conductivity. Suitable for large -scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105830090000071
    Figure BDA0005105830090000071
  • Figure BDA0005105830090000081
    Figure BDA0005105830090000081
Patent Text Reader

Abstract

The invention relates to the field of new energy batteries, in particular to a sulfide electrolyte composite material, a preparation method thereof and an all-solid-state battery, the sulfide electrolyte composite material comprises a core particle and a coating layer coating the surface of the core particle; wherein the inner core particle comprises sulfide solid electrolyte; the material of the coating layer comprises an amorphous compound; the amorphous compound comprises LiMX5Yn-1 / n, and M is selected from a group VB element and / or a group VIB element; x is a halogen element; n is greater than or equal to 1 and less than or equal to 3, and Yn-is at least one of NO3-, BO3 < 3->, BH4 <->, OH <->, O2 <->, BF4 <->, PO4 < 3->, N3 <->, SO4 < 2->, SO3 < 2->, S2 <-> and F <->. The sulfide electrolyte composite material provided by the invention can reduce the adsorption of moisture on the surface of the sulfide electrolyte, reduce the side reaction of the electrolyte and an active material under high voltage, reduce the interface impedance, make the solid-solid interface contact more stable, and have excellent chemical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy batteries, and in particular to a sulfide electrolyte composite material, a preparation method thereof, and an all-solid-state battery. Background Art

[0002] In recent years, safety issues and energy density constraints have caused the development of liquid batteries to face bottlenecks. The use of solid electrolytes to replace traditional electrolytes can solve the above problems. Sulfide electrolytes have been widely studied due to their high ionic conductivity, good mechanical strain and low density. However, sulfide electrolytes have poor chemical stability. The PS bonds in the electrolytes easily react with H2O and O2 in the air to cause irreversible reactions, resulting in structural damage and the production of toxic and harmful gases. In addition, during the electrochemical process, sulfide electrolytes will be continuously oxidized and decomposed at high voltages. The decomposition products will hinder the interfacial ion conduction, making the contact between the electrolyte and the active material worse, resulting in increased interfacial impedance. Therefore, the widespread application of sulfide electrolytes is hindered by chemical stability and electrochemical stability.

[0003] In response to the above problems, the prior art mainly constructs a coating layer on the surface of the material. Adv.Mater.2023,2300673 coats Al2O3 on the surface of sulfide solid electrolyte (LPSC) by atomic layer deposition (ALD), which improves the electrolyte's tolerance to water and oxygen and electrochemical stability, but ALD is difficult to apply to large-scale production applications. In addition, Chinese patent document CN110400967A proposes a three-layer core-shell structure electrolyte, but the core-shell structure significantly reduces the ionic conductivity of the electrolyte. Therefore, the current modification method is difficult to simultaneously meet the requirements of ionic conductivity, electrochemical stability, chemical stability and large-scale production applications. The use of compounds with ionic conductivity combined with low-temperature annealing methods to form a surface doped coating layer on the electrolyte surface can meet the above requirements at the same time. Summary of the invention

[0004] In view of this, the present invention is committed to providing a sulfide electrolyte composite material, a preparation method thereof and an all-solid-state battery, so as to solve the problems in the prior art that the sulfide electrolyte has poor air chemical stability, will be continuously oxidized and decomposed under high voltage, and the decomposition products will hinder the interfacial ion conduction.

[0005] In order to solve the above technical problems, this application is implemented as follows:

[0006] A first aspect of the present invention provides a sulfide electrolyte composite material, the sulfide electrolyte composite material comprising a core particle and a coating layer coated on the surface of the core particle;

[0007] Wherein, the core particles include a sulfide solid electrolyte; the coating layer material includes an amorphous compound;

[0008] The amorphous compound includes LiMX5Y n- 1 / n , wherein M is selected from Group VB elements and / or Group VIB elements; X is a halogen element; 1≤n≤3, Y n- NO3 - , BO3 3- 、BH4 - OH - , O 2- 、BF4 - PO4 3- 、N 3- 、SO4 2- 、SO3 2- , S 2- and F - At least one of .

[0009] Optionally, M is selected from at least one of Ta, Nb, W and Mo, and X is selected from at least one of F, Cl, Br and I.

[0010] Optionally, the ionic conductivity of the amorphous compound is ≥1 mS / cm.

[0011] Optionally, the sulfide solid electrolyte is selected from Li 7-p-q PS 6-p-q Cl p Z q , Li b NP c S d , at least one of aLi2S·(100-a)P2S5 and yLiI·zLiBr·(100-yz)(xLi2S·(100-x)P2S5); wherein Z is selected from at least one of F, Cl, Br and I, p≥0, q≥0; N is at least one of Sn, Ge and Si, b>0, c>0, d>0; 70≤a≤80; 70≤x≤80, 0≤y≤30, 0≤z≤30.

[0012] Optionally, the D50 of the sulfide solid electrolyte is 1 to 40 μm, preferably 3 to 15 μm; the thickness of the coating layer is ≤500 nm, preferably, the thickness of the coating layer is 5 to 200 nm.

[0013] A second aspect of the present invention provides a method for preparing a sulfide electrolyte composite material, the preparation method comprising the following steps:

[0014] S1, mixing a lithium-containing compound, a metal halide and a sulfide electrolyte to obtain a first material;

[0015] S2, sintering the first material;

[0016] Wherein, the metal element in the metal halide is selected from Group VB elements and / or Group VI B elements; the lithium-containing compound is at least one of LiCl, LiOH, LiBH4, LiBF4, LiNO3, Li2O, Li3BO3, Li2SO4, Li2SO3, Li3N and Li3PO4.

[0017] Optionally, the metal halide is selected from at least one of TaF5, NbF5, TaCl5, NbCl5, WCl5, MoCl5, TaBr5, NbBr5, TaI5 and NbI5.

[0018] Optionally, the ratio of the total mass of the lithium-containing compound and the metal halide to the mass of the sulfide electrolyte is (0.1% to 18%):1; preferably (0.1% to 10%):1.

[0019] Optionally, the sintering treatment conditions include: a temperature of 200 to 500° C. and a time of 0.5 to 6 hours.

[0020] A third aspect of the present invention provides an all-solid-state battery, which includes an electrolyte material, wherein the electrolyte material includes the above-mentioned sulfide electrolyte composite material or the sulfide electrolyte composite material prepared according to the above-mentioned preparation method.

[0021] Through the above technical solution, the beneficial technical effects of the present invention are:

[0022] (1) The sulfide electrolyte composite material of the present invention comprises a core particle and a coating layer coated on the surface of the core particle, wherein the coating layer material comprises an amorphous compound. The coating layer of the present invention can, on the one hand, inhibit the side reactions of the electrolyte and the active material under high voltage, reduce decomposition products, reduce interface impedance, and make the solid-solid interface contact more stable; on the other hand, it can reduce the adsorption of water and oxygen in the air on the surface of the material, reduce the generation of harmful gases, and effectively improve the chemical stability of the material.

[0023] (2) After the sulfide electrolyte composite material of the present invention is exposed to a dew point of -50°C, the ion conductivity retention rate is improved, and the comprehensive performance of the assembled all-solid-state battery is significantly improved.

[0024] (3) The coating layer on the surface of the sulfide electrolyte composite material of the present invention will not significantly affect the ionic conductivity of the sulfide electrolyte, and the preparation method is simple and easy to achieve large-scale application.

[0025] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0026] The present invention discloses a sulfide electrolyte composite material, a preparation method thereof and an all-solid-state battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0027] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0028] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0029] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0030] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0031] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0032] In order to solve the problem in the prior art that the sulfide electrolyte has poor air chemical stability and will be continuously oxidized and decomposed under high voltage, and the decomposition products will hinder the interfacial ion conduction, the present invention adopts the following technical solution:

[0033] A first aspect of the present invention provides a sulfide electrolyte composite material, the sulfide electrolyte composite material comprising a core particle and a coating layer coated on the surface of the core particle;

[0034] Wherein, the core particles include a sulfide solid electrolyte; the coating layer material includes an amorphous compound;

[0035] The amorphous compound includes LiMX5Y n- 1 / n , wherein M is selected from Group VB elements and / or Group VIB elements; X is a halogen element; 1≤n≤3, Y n- NO3 - , BO3 3- 、BH4 - OH - , O 2- 、BF4 - PO4 3- 、N 3- 、SO4 2- 、SO3 2- , S 2- and F - At least one of .

[0036] The sulfide electrolyte composite material of the present invention comprises a core particle and a coating layer coated on the surface of the core particle. By coating the surface of the sulfide solid electrolyte with an amorphous compound coating layer, the side reactions of the electrolyte and the active material under high voltage can be reduced, the decomposition products can be reduced, the interface impedance can be reduced, and the solid-solid interface contact can be made more stable; in addition, the amorphous compound coating layer can reduce the adsorption of water and oxygen in the air on the surface of the material, reduce the generation of harmful gases, and effectively improve the chemical stability of the sulfide electrolyte composite material.

[0037] According to the present invention, M may be selected from at least one of Ta, Nb, W and Mo, and X may be selected from at least one of F, Cl, Br and I.

[0038] For example, the amorphous compound in the present invention can be selected from LiTaCl6, LiTaCl5F, LiTaCl5Br, LiTaCl5I, LiTaCl5O 0.5 、LiTa 0.95 Nb 0.05 Cl 4.8 F 0.2 O 0.5、LiTaCl5BH4、LiTa 0.95 Nb 0.05 Cl 4.8 F 0.2 O 0.5 One of them.

[0039] In a preferred embodiment of the present invention, the ionic conductivity of the amorphous compound is ≥1 mS / cm.

[0040] According to the present invention, the sulfide solid electrolyte can be selected from Li 7-p-q PS 6-p-q Cl p Z q , Li b NP c S d , at least one of aLi2S·(100-a)P2S5 and yLiI·zLiBr·(100-yz)(xLi2S·(100-x)P2S5); wherein Z can be selected from at least one of F, Cl, Br and I, p≥0, q≥0; N can be at least one of Sn, Ge and Si, b>0, c>0, d>0; 70≤a≤80; 70≤x≤80, 0≤y≤30, 0≤z≤30.

[0041] Exemplarily, the sulfide solid electrolyte may be selected from Li6PS5C 1.0 , Li 5.7 PS 4.7 Cl 1.3 , Li 5.5 PS 4.5 C 1.0Br0.5 , Li 5.5 PS 4.5 Cl 1.5 , Li 5.4 PS 4.4 Cl 1.0 Br 0.6 , Li 10 GeP2S 12 、Li7P3S 11 and one of Li3PS4.

[0042] According to the present invention, the D50 of a suitable sulfide solid electrolyte can fully utilize the capacity of the active material. If the D50 of the sulfide solid electrolyte is too large, it may affect the full contact between the active material and the electrolyte. If the D50 of the sulfide solid electrolyte is too small, the ionic conductivity of the material may be low. The D50 of the sulfide solid electrolyte in the present invention may be 1 to 40 μm. Exemplarily, the D50 of the sulfide solid electrolyte may be any value among 1 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm and 40 μm or any value within the range of any two of the above values. Preferably, the D50 of the sulfide solid electrolyte is 3 to 15 μm.

[0043] According to the present invention, the thickness of the suitable coating layer can improve the chemical stability and electrochemical stability of the sulfide electrolyte composite material while maintaining the ionic conductivity of the sulfide electrolyte composite material. If the thickness of the coating layer is too large, the ionic conductivity of the sulfide electrolyte composite material may be greatly reduced. If the thickness of the coating layer is too small, it is easy to cause uneven coating. The thickness of the coating layer in the present invention is ≤500nm. Exemplarily, the thickness of the coating layer can be any value of 1nm, 50nm, 100nm, 200nm, 300nm, 400nm and 500nm or any value within the range of any two of the above values. Preferably, the thickness of the coating layer is 5nm to 200nm.

[0044] A second aspect of the present invention provides a method for preparing a sulfide electrolyte composite material, the preparation method comprising the following steps:

[0045] S1, mixing a lithium-containing compound, a metal halide and a sulfide electrolyte to obtain a first material;

[0046] S2, sintering the first material;

[0047] Wherein, the metal element in the metal halide is selected from Group VB elements and / or Group VI B elements; the lithium-containing compound is at least one of LiCl, LiOH, LiBH4, LiBF4, LiNO3, Li2O, Li3BO3, Li2SO4, Li2SO3, Li3N and Li3PO4.

[0048] The preparation method of the present invention mixes the refined sulfide electrolyte with the raw material of the surface coating material by dry or wet method, and then performs sintering treatment, so that the coating material generates a substance with ionic conductivity on the surface of the electrolyte. The coating layer on the surface of the electrolyte can improve the high-voltage resistance of the sulfide electrolyte; the coating layer material has good air stability, can reduce the adsorption of water and oxygen on the surface of the sulfide electrolyte, improve the structural stability, and thus inhibit the generation of toxic and harmful gases.

[0049] In a preferred embodiment of the present invention, by controlling the conditions of the sintering treatment, such as short-time low-temperature sintering treatment, some elements in the surface coating material can enter the surface layer of the sulfide electrolyte during the sintering process, which can further improve the stability of the electrolyte with water and oxygen in the air, alleviate the decomposition of the sulfide electrolyte at high voltage, reduce the interfacial impedance, and thus improve the electrochemical performance of the battery.

[0050] According to the present invention, the metal halide may be selected from at least one of TaF5, NbF5, TaCl5, NbCl5, WCl5, MoCl5, TaBr5, NbBr5, TaI5 and NbI5.

[0051] According to the present invention, the ratio of the total mass of the lithium-containing compound and the metal halide to the mass of the sulfide electrolyte may be (0.1% to 18%):1; preferably, the ratio of the total mass of the lithium-containing compound and the metal halide to the mass of the sulfide electrolyte may be (0.1% to 10%):1.

[0052] In step S1 of the present invention, the mixing treatment may be a ball milling treatment; illustratively, the conditions of the ball milling treatment may include: a rotation speed of 200 to 600 rpm and a time of 0.5 to 5 hours.

[0053] According to the present invention, the sintering conditions may include: a temperature of 200-500° C. and a time of 0.5-6 hours. The sintering atmosphere of the present invention may be nitrogen, argon, oxygen or a mixed gas thereof.

[0054] A third aspect of the present invention provides an all-solid-state battery, which includes an electrolyte material, wherein the electrolyte material includes the above-mentioned sulfide electrolyte composite material or the sulfide electrolyte composite material prepared according to the above-mentioned preparation method.

[0055] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.

[0056] Example 1

[0057] The raw materials 0.93g TaCl5, 0.03g TaF5, and 0.04g Li2O were added to 10g sulfide electrolyte Li 5.4 PS 4.4 Cl 1.0 Br 0.6 Among them, the D of sulfide electrolyte 50 The particle size was 5 μm and then ball milled at 300 rpm for 3 h to make the raw materials evenly dispersed on the surface of the sulfide electrolyte.

[0058] The sulfide electrolyte composite material LiTaCl was obtained by sintering in a tube furnace under an argon atmosphere at a temperature of 250°C for 3 hours. 4.8 F 0.2 O 0.5 @Li 5.4 PS 4.4 Cl 1.0 Br 0.6 The average thickness of the coating layer of the sulfide electrolyte composite material prepared in this embodiment is 120 nm.

[0059] Example 2

[0060] The raw materials 0.47g TaCl5 and 0.029g LiBH4 were added to 10g sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 Among them, the D of sulfide electrolyte 50 The particle size was 5 μm and then ball milled at 250 rpm for 4 h to make the raw materials evenly dispersed on the surface of the sulfide electrolyte.

[0061] Then, the sulfide electrolyte composite material LiTaCl5BH4@Li was obtained by sintering in a tubular furnace under a nitrogen atmosphere at a temperature of 220°C for 4 hours. 5.5 PS 4.5 Cl 1.5 The average thickness of the coating layer of the sulfide electrolyte composite material prepared in this embodiment is 50 nm.

[0062] Example 3

[0063] The raw materials 0.022g NbCl5, 0.54g TaCl5, 0.018g TaCl5, and 0.025g LiO2 were added to 10g sulfide electrolyte Li 5.7 PS 4.7 Cl 1.3 Among them, the D of sulfide electrolyte 50 The particle size was 5 μm and then ball milled at 350 rpm for 1 h to make the raw materials evenly dispersed on the surface of the sulfide electrolyte.

[0064] The sintering process was then carried out in a box furnace under a nitrogen atmosphere at a temperature of 240° C. for 3.5 h to obtain the sulfide electrolyte composite material LiTa of this embodiment. 0.95 Nb 0.05 Cl 4.8 F 0.2 O 0.5 @Li 5.7 PS 4.7 Cl 1.3 The average thickness of the coating layer of the sulfide electrolyte composite material prepared in this embodiment is 70 nm.

[0065] Comparative Example 1

[0066] 10g D 50 5μm sulfide electrolyte Li 5.4 PS 4.4 Cl 1.0 Br 0.6 Ball milling was performed at 300 rpm for 3 h.

[0067] Then, the sulfide electrolyte material Li of this comparative example was sintered in a tube furnace under an argon atmosphere at a sintering temperature of 250° C. for 3 h. 5.4 PS 4.4 Cl 1.0 Br 0.6 .

[0068] Comparative Example 2

[0069] 10g D 50 5μm sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 Ball milling was performed at 250 rpm for 4 h.

[0070] The sulfide electrolyte composite material Li 5.5 PS 4.5 Cl 1.5 .

[0071] Comparative Example 3

[0072] 10g D 50 5μm sulfide electrolyte Li 5.7 PS 4.7 Cl 1.3 The sulfide electrolyte composite material Li 5.7 PS 4.7 Cl1.3 .

[0073] Test Example 1

[0074] The sulfide electrolyte materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were exposed to a dew point of -50°C for 60 min and 120 min, and 150 mg of powder was weighed and placed in a battery mold (inner diameter 10 mm), and a pressure of 100 MPa was applied. The AC impedance was tested using an electrochemical workstation, and an external voltage of 20 mV was applied in the frequency range of 1 Hz to 7 MHz. The ionic conductivity of the halide electrolyte after different exposure times was calculated, and the test results are shown in Table 1. Among them, the impedance value of each material was tested by the AC impedance method, and the ionic conductivity was calculated according to σ=L / RS (σ is ionic conductivity, L is the thickness of the electrolyte sheet, R is the impedance value, and S is the electrolyte area). The test results are shown in Table 1.

[0075] Table 1

[0076]

[0077] It can be seen from Table 1 that the ionic conductivity of the sulfide electrolyte composite materials prepared in Examples 1 to 3 after being exposed to air is better than that of the sulfide electrolytes in Comparative Examples 1 to 3.

[0078] Test Example 2

[0079] The electrolyte materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were exposed to a dew point of -50°C for 60 minutes, and then added to the ternary composite positive electrode to prepare a positive electrode layer (the positive electrode layer contains a ternary positive electrode material, an electrolyte exposed to a dew point of -50°C, a conductive agent, and a binder, with a mass ratio of 70:26.5:3:0.5), and each sulfide electrolyte material that has not been exposed is used as an electrolyte layer, and metallic lithium is used as a negative electrode to assemble an all-solid-state battery. Specifically:

[0080] (1) The preparation method of the positive electrode sheet includes: mixing a ternary positive electrode material, a solid electrolyte exposed for 60 minutes, a conductive agent (VGCF) and a binder (PTFE) in a mass ratio of 70:26.5:3:0.5 to prepare a positive electrode film, and compounding the positive electrode film with aluminum foil to form a positive electrode sheet, that is, obtaining a positive electrode sheet.

[0081] (2) Using lithium metal negative electrode as the negative electrode sheet.

[0082] (3) The method for preparing a solid electrolyte membrane comprises: fully mixing each sulfide electrolyte material that has not been exposed with a binder (PTFE) at a mass ratio of 100:0.6 to prepare a solid electrolyte membrane.

[0083] (4) The battery assembly method includes: using a roller press to composite the metal lithium negative electrode with the solid electrolyte membrane, and then assembling it with the positive electrode (positive electrode sheet) into an all-solid-state battery.

[0084] The electrochemical performance of the prepared all-solid-state battery was tested, and the test results are shown in Table 2.

[0085] Among them, the method for the first charge and discharge test includes: subjecting the prepared all-solid-state battery to a 0.1C constant current charge and discharge test for one cycle at 25°C, with a voltage range of 2.7-4.3V.

[0086] The rate test method includes: charging and discharging the prepared all-solid-state battery at 25°C, with constant currents of 0.2C, 0.5C, and 2C for 5 cycles respectively, with a voltage range of 2.7-4.3V.

[0087] The long cycle test method includes: charging and discharging the prepared all-solid-state battery for 100 cycles at 0.1C constant current at 25°C with a voltage range of 2.7-4.3V.

[0088] Table 2

[0089]

[0090] It can be seen from Table 2 that the first discharge specific capacity, first coulombic efficiency, cycle performance and rate performance of the electrolyte material prepared in the embodiment after being exposed to a dew point of -50°C for 60 minutes are significantly improved.

[0091] Combining the data in Table 1 and Table 2, the sulfide electrolyte composite material of the present invention reduces the adsorption of water on the surface of the sulfide electrolyte. After exposure at a dew point of -50°C, the decomposition products of the electrolyte are reduced, the ion conductivity retention rate is improved, and the chemical stability of the electrolyte is effectively improved. The high-voltage resistance of the halide reduces the decomposition products in the electrochemical process, the solid-solid interface contact is more stable, and the interface impedance is reduced, which effectively improves the electrochemical performance of the battery.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A sulfide electrolyte composite material, characterized in that: The sulfide electrolyte composite material comprises a core particle and a coating layer coated on the surface of the core particle; Wherein, the core particles include a sulfide solid electrolyte; the coating layer material includes an amorphous compound; The amorphous compound includes LiMX5Y n- 1 / n , wherein M is selected from Group VB elements and / or Group VIB elements; X is a halogen element; 1≤n≤3, Y n- NO3 - , BO3 3- 、BH4 - OH - , O 2- 、BF4 - PO4 3- 、N 3- 、SO4 2- 、SO3 2- , S 2- and F - At least one of .

2. The sulfide electrolyte composite material according to claim 1, characterized in that M is selected from at least one of Ta, Nb, W and Mo, and X is selected from at least one of F, Cl, Br and I.

3. The sulfide electrolyte composite material according to claim 1, characterized in that The ionic conductivity of the amorphous compound is ≥1 mS / cm.

4. The sulfide electrolyte composite material according to claim 1, characterized in that: The sulfide solid electrolyte is selected from Li 7-p-q PS 6-p-q Cl p Z q , Li b NP c S d , at least one of aLi2S·(100-a)P2S5 and yLiI·zLiBr·(100-yz)(xLi2S·(100-x)P2S5); wherein Z is selected from at least one of F, Cl, Br and I, p≥0, q≥0; N is at least one of Sn, Ge and Si, b>0, c>0, d>0; 70≤a≤80; 70≤x≤80, 0≤y≤30, 0≤z≤30.

5. The sulfide electrolyte composite material according to claim 1, characterized in that: The D50 of the sulfide solid electrolyte is 1 to 40 μm, preferably 3 to 15 μm; The thickness of the coating layer is ≤500nm. Preferably, the thickness of the coating layer is 5nm to 200nm.

6. A method for preparing the sulfide electrolyte composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1, mixing a lithium-containing compound, a metal halide and a sulfide electrolyte to obtain a first material; S2, sintering the first material; Wherein, the metal element in the metal halide is selected from Group VB elements and / or Group VI B elements; the lithium-containing compound is at least one of LiCl, LiOH, LiBH4, LiBF4, LiNO3, Li2O, Li3BO3, Li2SO4, Li2SO3, Li3N and Li3PO4.

7. The preparation method according to claim 6, characterized in that: The metal halide is selected from at least one of TaF5, NbF5, TaCl5, NbCl5, WCl5, MoCl5, TaBr5, NbBr5, TaI5 and NbI5.

8. The preparation method according to claim 6, characterized in that: The ratio of the total mass of the lithium-containing compound and the metal halide to the mass of the sulfide electrolyte is (0.1% to 18%):1; preferably (0.1% to 10%):

1.

9. The preparation method according to claim 6, characterized in that: The sintering conditions include: a temperature of 200 to 500° C. and a time of 0.5 to 6 hours.

10. An all-solid-state battery, characterized in that: The all-solid-state battery includes an electrolyte material, wherein the electrolyte material includes the sulfide electrolyte composite material according to any one of claims 1 to 5 or the sulfide electrolyte composite material prepared according to the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Sulfide solid electrolyte of three-layer core-shell structure, preparation method thereof and all-solid-state battery

    CN110400967A

Cited By

  • Solid electrolyte material, preparation method thereof and battery

    CN120413777A

  • Electrode material additive and preparation method and application thereof

    CN120709375A